(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Аннотация: В статье представлена информация об основных методах профилактики брадзота и эффективности вакцин, разработке оптимальных методов количественного контроля напряженности иммунитета и специфической профилактики клостридиоза, созданных учеными разных стран. Summary: This article provides information on the main methods of prevention of bradzot disease and the effectiveness of vaccines, the development of optimal methods of quantitative control of the intensity of immunity, and specific prevention of clostridiosis created by scientists from different countries